The Analysis of Economic Sector Potential in Surabaya using Location Quotient, Shift Share, and Klassen Typology in 2015-2019 - Ray Julio Pangow; Alen Memah; D. Busdan; Rorong, Ita P. F.; Mauna Th. B. Maramis (Open Access Indonesia Journal of Social Sciences, 2023)
Economic development in an area requires encouragement between the local government and the community to grow regional economic activities by managing existing resources, establishing relationships between government and private agencies, and encouraging development related to regional economic activities. The development of a region cannot be separated from national development because regional governments and local communities need coordination to utilize, create, develop, and produce existing resources. This study aimed to describe the potential of the economic sector in Surabaya in the period of 2015-2019. This research uses secondary data for five years in the 2015-2019 period. The analytical method used analyzes location quotient, shift share, and Klassen typology. The results of the study revealed that five sectors were included in quadrant I, and two sectors were included in quadrant IV. In conclusion, Surabaya has fifteen economic sectors that drive economic progress, ten sectors grow relatively fast, nine industries have outstanding location advantages, and five sectors belong to quadrant I. This research is used as a reference in making policies related to economic progress in Surabaya, which impacts increasing employment and per capita income.